2018
DOI: 10.3389/fneur.2018.01010
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Elastography of Rodent Brain

Abstract: Magnetic resonance elastography (MRE) is a non-invasive imaging technique, using the propagation of mechanical waves as a probe to palpate biological tissues. It consists in three main steps: production of shear waves within the tissue; encoding subsequent tissue displacement in magnetic resonance images; and extraction of mechanical parameters based on dedicated reconstruction methods. These three steps require an acoustic-frequency mechanical actuator, magnetic resonance imaging acquisition, and a post-proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…An experiment involving mouse brain elastography using LSW was performed and demonstrated that the cerebellum and midbrain were found to be softer than the cerebral cortex. This is consistent with various magnetic resonance elastography studies which have shown similar findings in both mice and humans [25,[33][34][35]. In these studies, a general trend for shear storage modulus is from 4 kPa to 16 kPa for the cerebral cortex, and from 1 kPa to 4 kPa for the cerebellum/midbrain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An experiment involving mouse brain elastography using LSW was performed and demonstrated that the cerebellum and midbrain were found to be softer than the cerebral cortex. This is consistent with various magnetic resonance elastography studies which have shown similar findings in both mice and humans [25,[33][34][35]. In these studies, a general trend for shear storage modulus is from 4 kPa to 16 kPa for the cerebral cortex, and from 1 kPa to 4 kPa for the cerebellum/midbrain.…”
Section: Discussionsupporting
confidence: 91%
“…The gel in between the coverslip and brain tissue (thickness ∼0.1 mm) serves as an elastic coupling medium. The shear wave speed in the 2% concentration agarose gel was measured to be 2.67 ± 0.05 m/s, which is in the range of previously reported shear wave speed in mouse brain [25] and avoids the creation of strong wave reflections.…”
Section: Sample Preparation and Characterizationsupporting
confidence: 57%
“…Magnetic resonance elastography (MRE) could represent a promising alternative to the use of GBCA. MRE provides information about the mechanical properties of tissues (7,8) by analyzing their response to oscillatory shear stress (9). Using MRE, we reported on reduced brain viscoelasticity in patients with clinically isolated syndrome (10) as well as patients with established relapsing-remitting (11) and chronic-progressive (12) MS.…”
Section: Introductionmentioning
confidence: 99%
“…The research of Bigot et al performed on a relapsing-remitting EAE model shows that a reduction of brain stiffness correlates with clinical disability and is associated with enhanced expression of the extracellular matrix protein fibronectin. These results taken together suggest that MRE could potentially emerge as a safe tool to monitor MS activity [83].…”
Section: Alternative Non-contrast-enhanced Techniques Of Mrimentioning
confidence: 71%